STUDI ANALISIS KEBIJAKAN PENDIDIKAN DAN PELATIHAN DALAM UPAYA MENINGKATKAN KINERJA PEGAWAI DI BADAN KEPEGAWAIAN DAN PENDIDIKAN PELATIHAN KOTA CIREBON (Studi Kasus Diklat Teknis) - Agus Gunawan; Achdi Halim; Nurudin Siraj (Jurnal Ilmiah Publika, 2015)
ABSTRACT The study entitled "Study of Education Policy and Training Studies in an Effort to Improve Employee Performance in the Civil Service Agency and Training Education in Cirebon City (Case Study of Technical Training)". The title was raised because the employee's performance was caused by the lack of optimal implementation of education and training program policies, therefore it was suspected that the implementation of education and training program had an impact on employee performance which was still not optimal in accordance with the targets achieved. The implementation of Education and Training Policies that are still not optimal is felt to affect the performance of employees, because it can hamper the interests of the implementation of duties, the implementation of cooperative relationships, and the interests of the results achieved in the organization. This study aims to find out directly in the implementation of education and training programs in improving employee performance, to determine the inhibiting factors of employee performance at the Cirebon City Personnel Training and Education Agency. The study was conducted using qualitative research methods, this method uses data collection techniques: library studies, interviews, observation, documentation. The study was conducted at the Cirebon City Personnel and Education Training Agency, with Secretary informants and other employee. The results of the study: 1) the implementation of education and training programs is not optimal with the existing policies that cause adverse impacts on employee performance, 2) The inhibiting factors of the implementation of education and training policies are due to the quality of human resources that are not optimal, and 3) supporting factors the implementation of education and training policies has the capability of the implementing apparatus and the Civil Service Standard Operating Procedure as a guide in working.